Spiritualizing Holistic Education in the 21st Century: An Overview of Islamic and Western Perspectives - Rofhani, Rofhani; Yusuf, M.; YS, Arbaiyah (FIKROTUNA: Jurnal Pendidikan dan Manajemen Islam, 2025)
This study examines the spiritualization of holistic education in the 21st century from Islamic and Western perspectives, highlighting the differences and similarities in spiritual paradigms that play a crucial role in shaping well-rounded individuals. The Islamic perspective emphasizes the values of tawhid, tazkiyah, and amanah, which lead to moral and ethical development. In contrast, the Western perspective focuses more on self-awareness, mindfulness, and social responsibility, promoting mental and emotional balance. Despite having different philosophical foundations, both perspectives contribute to the same educational goal: character formation and social awareness. This study also identifies the significance of the spiritual paradigm in addressing modern global challenges, such as mental health crises and social inequalities.